Monitoring serum proangiogenic cytokines from hepatocellular carcinoma patients treated with sorafenib. Issue 6 (10th December 2018) - Adachi, Takuya; Nouso, Kazuhiro; Miyahara, Koji; Oyama, Atsushi; Wada, Nozomu; Dohi, Chihiro; Takeuchi, Yasuto; Yasunaka, Tetsuya; Onishi, Hideki; Ikeda, Fusao; Nakamura, Shinichiro; Shiraha, Hidenori; et al.
Abstract: Background and Aim: Several factors, including proangiogenic cytokines, have been reported as predictive markers for the treatment effect of sorafenib in patients with hepatocellular carcinoma (HCC); however, most of them were determined based on one‐time measurements before treatment. Methods: We consecutively recruited 80 advanced HCC patients who were treated with sorafenib prospectively. Serum levels of eight proangiogenic cytokines and the appearance of adverse events were monitored periodically, and their correlations with the prognoses of the patients were evaluated. Results: Among six significant risk factors for overall survival in univariate analyses, high angiopoietin‐2 (hazard ratio, 2.06), high hepatocyte growth factor (hazard ratio, 2.08), and poor performance status before the treatment (hazard ratio, 2.48) were determined as independent risk factors. In addition, high angiopoietin‐2 at the time of progressive disease was a marker of short post‐progression survival (hazard ratio, 4.27). However, there was no significant variable that predicted short progression‐free survival except the presence of hepatitis B virus surface antigen. Conclusions: Predictions of overall survival and post‐progression survival were possible by periodically measuring serum proangiogenic cytokines, especially angiopoietin‐2, in patients with HCC treated with sorafenib.